A STUDY ON PATTERN OF PRESCRIBING MEDICATIONS USED IN SECONDARY PREVENTION OF STROKE - Kc, Jithin; G, Arya; Nair, Lekshmi P; R, Lakshmi (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objectives: The main objectives of this study were to estimate the demographic details of patients with the first incidence of stroke and to study the various risk factors for ischemic stroke. Methods: It was a retrospective, observational study carried out for 1 year at the Department of Stroke Medicine of a tertiary care teaching hospital in Kerala, India. A total of 636 patients were admitted under stroke medicine during the period from July 1, 2014, to July 1, 2015, and who satisfied the inclusion and exclusion criteria were included in the study. A standardized data collection form was prepared and necessary data were collected from patient’s medical records. Results: The maximum number of patients was in the age group of 60-69 years. 65.1% patients were residing in the rural area. 60.7% patients were male. Most of them had hypertension as common comorbidity (21.35%) and the highest number of patients had diabetes mellitus and hypertension (21.7%). Majority of the patients were prescribed with antiplatelets (94.91%), followed by statins (93.8%). Conclusion: A strict control on the comorbid conditions and sticking on to the medications can prevent the occurrence of future stroke. Keywords: Stroke, Secondary prevention, Drugs, Prescribing pattern.